2022
DOI: 10.54905/disssi/v26i119/ms26e1947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alexithymia and the influencing factors among medical students at Umm Al-Qura University: A cross-sectional study

Abstract: Background: Alexithymia is inability of the person to describe his emotions, somatic sensations, and struggle to discuss feelings. Objectives: To determine the prevalence of the state of alexithymia among undergraduate medical students and to explore its potential risk factors. Methods: A cross-sectional study was done through online survey targeted to undergraduate medical students. The survey included the Toronto Alexithymia Scale (TAS-20), students' socio-demographics, and the potential risk factors for ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…The current study reported female medical students had a higher risk of developing alexithymia compared to male students. This finding is consistent with the findings of several studies, including Hamaideh et al [ 4 ] and Alharthi et al [ 30 ], which state that females are more likely to develop emotional problems, which explains why they are more likely to develop alexithymia. In contrast, a study carried out by Zhu et al [ 14 ] revealed that male medical students were at higher risk for alexithymia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current study reported female medical students had a higher risk of developing alexithymia compared to male students. This finding is consistent with the findings of several studies, including Hamaideh et al [ 4 ] and Alharthi et al [ 30 ], which state that females are more likely to develop emotional problems, which explains why they are more likely to develop alexithymia. In contrast, a study carried out by Zhu et al [ 14 ] revealed that male medical students were at higher risk for alexithymia.…”
Section: Discussionsupporting
confidence: 93%
“…The current study assessed the prevalence of alexithymia among medical students in Saudi Arabia and evidenced that alexithymia was associated with sociodemographic factors (such as female, having a chronic disease, and income) and depression. As per the TAS-20 scale, the sample of this study showed a lower prevalence of alexithymia (47.3%) than other studies among medical students in other Saudi cities such as Jeddah (49%) [ 14 ], and Makkah (56.5%) [ 30 ]. However, we found a higher prevalence of alexithymia than a previous study conducted in the Kingdom of Saudi Arabia, which reported that 30.2% of university students had alexithymia and 33.8% had possible alexithymia [ 39 ].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…A s described in the literature, alexithymia is a multi-facet construct with difficulty in recognizing, describing, and distinguishing between emotions and bodily tensions related to emotional excitement and having difficulty expressing feelings for others. 1 The common signs of this construct include (a) trouble recognizing emotions and feelings, (b) difficulty recognizing vibes of passionate excitement, and (c) limitation in imagination and dreaming. 2 The prevalence of alexithymia has been found in most previous studies to be approximately 10% among the general population.…”
mentioning
confidence: 99%